2014
DOI: 10.4081/pmc.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous gastric rupture in a 5 years girl

Abstract: We describe a case of spontaneous gastric rupture in a child of 5 years old. The patient reached us in a serious condition; the anamnesis was negative for traumatic events or gastrointestinal disorders. An abdominal X-ray and CT scan revealed free air and fluid in the abdominal cavity, leading to the diagnosis of gastro-intestinal perforation. Submitted to urgent surgery, a rupture of the posterior wall of the stomach was found that was treated with gastrectomy "à la demande". The surgery follow-up was regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Fukata et al reported that the etiology of spontaneous gastric rupture in children was similar to that in neonates, as revealed by the pathological ndings of a muscle defect [8]. Additionally, Salerno et al revealed abnormal gastric wall development in a 5-year-old girl during pathological examination [9]. However, in 1965, Shaw et al explored this theory by tying the esophageal and duodenal ends of the stomach in dogs and in ating them until the organ perforated.…”
Section: Etiologymentioning
confidence: 99%
“…Fukata et al reported that the etiology of spontaneous gastric rupture in children was similar to that in neonates, as revealed by the pathological ndings of a muscle defect [8]. Additionally, Salerno et al revealed abnormal gastric wall development in a 5-year-old girl during pathological examination [9]. However, in 1965, Shaw et al explored this theory by tying the esophageal and duodenal ends of the stomach in dogs and in ating them until the organ perforated.…”
Section: Etiologymentioning
confidence: 99%